Analysis of lateral binding force exerted on multilayered spheres induced by high-order Bessel beams with arbitrary polarization angles. (December 2018) - Bai, J.; Wu, Z.S.; Ge, C.X.; Shang, Q.C.; Li, Z.J.; Gong, L.
Highlights: The lateral binding force exerted on an aggregate of multilayered spheres induced by high-order Bessel beam with arbitrary polarization angles is studied analytically. The accuracy of the theory and codes is verified. Numerical effects of various parameters and different properties are numerically analyzed in detail. Abstract: Based on the generalized multi-particle Mie equation (GMM) and Electromagnetic Momentum (EM) theory, the lateral binding force (BF) exerted on multilayered spheres induced by an arbitrary polarized high-order Bessel beam (HOBB) is investigated with particular emphasis on the half-conical angle of the wave number components and the order (or topological charge) of the beam. The illuminating HOBB with arbitrary polarization angle is described in terms of beam shape coefficients (BSCs) within the framework of generalized Lorenz-Mie theories (GLMT). Utilizing the addition theorem of the spherical vector wave functions (SVWFs), the interactive scattering coefficients are derived through the continuous boundary conditions on which the interaction of the multilayered spheres is considered. Numerical results concerning the influences of different parameters of the incident Bessel beam and of the binding body on the lateral BF are displayed in detail. The observed dependence of the separation of optically bound particles on the incidence of HOBB is in agreement with earlier theoretical prediction. Accurate investigation of BF induced by HOBB exerted on multilayered spheres could provide key support for further research on optical binding between more complex multilayered biological cells, which plays an important role in using optical manipulation on stratified particle self-assembly.